Improving domestic violence screening practices in the emergency department: an Australian perspective. Issue 2 (14th March 2022) - Sweeny, Amy Lynn; Bourke, Caitlin; Torpie, Thomas Martin; Sargeant, Sally; Hughes, James; Watson, Julie; Conroy, Sheree; Carrasco, Angel; Tighe, Kym; Thornton, Neale Stuart; Cumner, Amber-Shea; Baird, Kathleen
Abstract : Introduction: Domestic violence (DV) is a major cause of morbidity worldwide. The ED is a location recommended for opportunistic screening. However, screening within EDs remains irregular. Objective: To examine intrinsic and extrinsic barriers to routine screening in Australian EDs, while describing actions taken after identification of DV. Methods: Emergency clinicians at nine public hospitals participated in an anonymous online survey. Factor analysis was performed to identify principal components around attitudes and beliefs towards screening. Results: In total, 496 emergency clinicians participated. Universal screening was uncommon; less than 2% of respondents reported screening all adults or all women. Although willing, nearly half (45%) reported not knowing how to screen. High patient load and no single rooms were 'very or severely limiting' for 88% of respondents, respectively, while 24/7 social work and interpreter services, and online/written DV protocols were top enablers. Factor analysis identified four distinct intrinsic belief components: (1) screening is not futile and could be done in ED, (2) screening will not cause harm, (3) there is a duty to screen and (4) I am willing to screen. Conclusion: This study describes a culture of Queensland ED clinicians that believe DV screening in ED is important and interventions are effective. Most ED clinicians are willing to screen. In this setting, availability of social work and interpreter services are important mitigating resources. Clinician education focusing on duty to screen, coupled with a built-in screening tool, and e-links to a local management protocol may improve the uptake of screening and subsequently increase detection.